Rice stripe mosaic virus encoded phosphoprotein forms viral factory-like granules and is crucial for viral replication - Zhiyi Wang; Jingyi Zhang; Xinyue Song; Siping Chen; Xue Cao; Xin Yang; Guohui Zhou; Tong Zhang (Phytopathology Research)
Abstract Viral proteins can aggregate into granules within host cells, known as viral factories, or viroplasms, which play a pivotal role in facilitating viral replication and shielding the viral genome from cellular defense mechanisms. Rice stripe mosaic virus (RSMV), a plant cytorhabdovirus, is notorious for causing significant damage to rice production. Despite its impact, the mechanisms underlying the replication and assembly of RSMV remain largely unexplored. In this investigation, we established a minireplicon (MR) system of RSMV in Nicotiana benthamiana plants to assess the influence of RSMV phosphoprotein (P) on viral replication. Our findings indicate that RSMV P forms viral factory-like granules and is an important component of viral factories. Further investigation showed that the formation of P granules is indispensable for MR replication. Through deletion analysis, we identified the IDR2 region of P as crucial for granule formation and MR replication. These findings underscore the necessity of P protein granule formation in viral replication.